New Publications Of The Bureau Of Mines ? List 941 - September-October 1995 - Electronic Information (The National Institute for Occupational Safety and Health (NIOSH), 1995)
Many USBM research and information products are available through the systems or formats listed below: Mines FaxBack: Return fax service. 1. Use the touch-tone handset attached to your fax machine's telephone jack. (ISDN [digital] telephones cannot be used with fax machines.) 2. Dial 202/219 3644. 3. Listen to the menu options and punch in the number of your selection, using the touch-tone telephone. 4. After completing your selection, press the start button o your fax machine. Mines Data: Computer bulletin board. Log on via modem through 202/501-0373, or call 202/501-0406 for technical assistance. CD-ROM: This USBM disk is updated quarterly and sold by GPO's Superintendent of Documents. For information on the latest product, please contact Rodger Wedgeworth, 202/501-9557. Internet/World Wide Web: Text and graphics. Access via PC-based browsing software such as Netscape or Mosaic. Universal Resource Locator (URL) is: http:/www.usbm.gov Internet/Gopher Server Text and tables only. Using Gopher client software, access via port 70 as follows: gopher.usbm.gov Internet System Administrator: webmaster@usbm.gov (or contact your local System Administrator).